2021
DOI: 10.3168/jds.2020-18772
|View full text |Cite
|
Sign up to set email alerts
|

Infrared milk analyzers: Milk urea nitrogen calibration

Abstract: Our first objective was to redesign a modified 14-sample milk calibration sample set to obtain a welldistributed range of milk urea nitrogen (MUN) concentrations while maintaining orthogonality with variation in fat, protein, and lactose concentration. Our second objective was to determine the within-and betweenlaboratory variation in the enzymatic spectrophotometric method on the modified milk calibration samples and degree of uncertainty in MUN reference values, and then use the modified milk calibration sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The p-values>0.05 confirming significance of the instrument effects throughout all 177 weeks confirms this, while the weekday variations within each instrument were significant for only two of the 177 weeks. Recent work on minor milk components such as milk urea has also shown the impact of inter instrument differences on IR predicted results (Wood et al, 2020;Portenoy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-values>0.05 confirming significance of the instrument effects throughout all 177 weeks confirms this, while the weekday variations within each instrument were significant for only two of the 177 weeks. Recent work on minor milk components such as milk urea has also shown the impact of inter instrument differences on IR predicted results (Wood et al, 2020;Portenoy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on minor milk components such as milk urea has also shown the impact of inter instrument differences on IR predicted results. (Wood et al, 2020;Portenoy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Modified Milk Calibration Sample Set to Evaluate Method Performance. Modified milk calibration samples (14 milk samples per set), prepared in the Cornell University Pilot Plant as described by Kaylegian et al (2006), and as modified by Portnoy et al (2021), were shipped to a total of 9 laboratories, where they were analyzed by reference chemical methods for all the main milk components and MUN. The methods used to determine fat, protein, and lactose in the sample set were the following validated methods (AOAC International, 2019c): for fat, Mojonnier ether extraction (Barbano et al, 1988;AOAC International, 2019c; method 989.05); for true protein, Kjeldahl analysis for direct protein nitrogen determination (Barbano et al, 1991;AOAC International, 2019c;method 991.22); for lactose, spectrophotometric enzymatic analysis (Lynch et al, 2007;AOAC International, 2019c;method 2006.06).…”
Section: Performance Evaluation Of the Enzymatic Spectrophotometric Mun Methodsmentioning
confidence: 99%
“…Mitchell et al (2005) also found that the infrared predictions showed greater heritability than the wet chemistry MU values (0.22 vs. 0.15, respectively). Recently, Portnoy et al (2021) pointed out, when using a PLS model to predict the urea content of milk, that careful attention needs to be given to modeling the background variation in milk fat, true protein, and lactose, as they are correlated with the urea content.…”
Section: Descriptive Statistics and Main Sources Of Variation In Milk...mentioning
confidence: 99%